(3TQM deY GdCOdIs - (3YHO Gddg Hf eMeO Hf GdJdeSGfis; (3CHj GdeYGdj YHO Gdedc Hf YHO Gddg Hf jhSa GdLhjfj, EeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3GdMeO gh GdKfGA Ydi Gddg HPcQ ChUGa LdGdg hceGdg hbO jSJYed GdMeO ehVY GdTcQ s
(3BNQgG (B:s
(3hgPg GdfHPi GdePchQI cGajI ai gPG GdHGH , hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
Keywords: (3GdJhMjO hGdedd hGdfMds